Economia circular e destinação de vestuário descartado: práticas organizadas por cooperativas de reciclagem em Cascavel-PR - Cardoso, Claudio Cesar Gomes (2023)
The increase in initiatives for the correct disposal of waste, the concern with sustainable development combined with the need to reduce the exploitation of natural resources, has contributed to an awareness of protection of our environment. This has led to the creation and strengthening of projects for the correct disposal of waste in various spheres of industry and society in general. An example is the door-to-door recycling material collection projects, which take place in the city of Cascavel, state of Paraná, where all the collected material is taken to the city's recycling centers, providing material for recycling cooperatives, generating mechanisms for reusing recyclable materials in general, contributing to a sustainable vision, paving the way for the production of new products and businesses. This research aimed to analyze the circular economy practices in the disposal of discarded clothing organized by recycling cooperatives in Cascavel, considering the dimensions of sustainability. The research was carried out through a qualitative approach, where semi-structured interviews were used. Managers, administrative technicians and members of the recycling cooperatives of the city’s ecopoints were interviewed. The analysis and interpretation of the research data indicated the presence of initiatives to reuse clothing material in two of the six ecopoints of the municipality, where the following items were identified: disposal activities of discarded clothing, the volume of discarded clothing used in bazaars and donation and also the volume of what does not go to the municipal landfill, contributing to the environment. One of the benefits identified in this research was the increase in the income of members in the two cooperatives that carry out circular economy initiatives. Through the sale in bazaars, the amount collected has helped in the general expenses of the cooperatives and the rest of the amount is monthly divided among the members. This research contributes to the community, showing the circular economy initiatives that already occur in the cooperatives of Cascavel and also showing how the collection, separation and disposal of discarded clothing are carried out. These initiatives increase the useful life of garments, contributing to the generation of income for cooperative members, and can be replicated in other recycling cooperatives in the municipality and other regions of the country.